The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1590/s0102-865020160080000007
|View full text |Cite
|
Sign up to set email alerts
|

Tibial and fibular nerves evaluation using intraoperative electromyography in rats

Abstract: Intellectual and scientific content of the study. ABSTRACT PURPOSE:To evaluate a new model of intraoperative electromyographic (EMG) assessment of the tibial and fibular nerves, and its respectives motor units in rats. METHODS:Eight Wistar rats underwent intraoperative EMG on both hind limbs at two different moments: week 0 and week 12.Supramaximal electrical stimulation applied on sciatic nerve, and compound muscle action potential recorded on the gastrocnemius muscle (GM) and the extensor digitorum longus mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
0
14
0
5
Order By: Relevance
“…There is no telling if the electrical stimulus used in the preoperative period was supramaximal or if the intensity was maintained or increased during the experiment, which could cause current leakage and an abnormally high CMAP in response . (3) The stimulating and measuring electrodes were on opposite sides of the surgical field, however, no standardized distance was established between them, which could produce abnormal CMAP results or contamination of electrophysiological answers by branches of the sciatic, sural, tibia, or fibular nerves . (4) The author evaluates CMAP amplitude but not duration or latency, which are also important when considering nerve function.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is no telling if the electrical stimulus used in the preoperative period was supramaximal or if the intensity was maintained or increased during the experiment, which could cause current leakage and an abnormally high CMAP in response . (3) The stimulating and measuring electrodes were on opposite sides of the surgical field, however, no standardized distance was established between them, which could produce abnormal CMAP results or contamination of electrophysiological answers by branches of the sciatic, sural, tibia, or fibular nerves . (4) The author evaluates CMAP amplitude but not duration or latency, which are also important when considering nerve function.…”
Section: Discussionmentioning
confidence: 99%
“…The author also reported that distal motor and sensory axon counts were higher in polyethylene glycol‐treated rats. However, in addition to all the problems mentioned in the paragraph above about methodology used for the functional evaluation tests, the authors used female rats that undergo hormonal changes that alters neural regeneration …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations